Intercropping Onion and Garlic with Brinjal Under Different Planting System (Bangladesh Agronomy Journal, 2025)
The experiment was conducted at the Agronomy Research Field of Bangladesh Agricultural Research Institute, Gazipur during rabi season of 2019-2020 and 2020-21 to find out the suitable crop combination of onion and garlic with brinjal for increasing total productivity, economic return and maximize land utilization through intercropping system. Seven treatments viz., T1= Brinjal (80 cm × 60 cm) 100% + 4 row onion (15 cm × 10 cm) 57%, T2= Brinjal (80 cm × 60 cm) 100% + 3 row onion (15 cm × 10 cm) 43%, T3= Brinjal (80 cm × 60 cm) 100% + 4 row garlic (15 cm × 10 cm) 57%, T4= Brinjal (80 cm × 60 cm) 100% + 3 row garlic (15 cm × 10 cm) 43%, T5= Sole brinjal (80 cm × 60 cm) 100%, T6= Sole onion (15 cm × 10 cm) 100%, T7= Sole garlic (15 cm × 10 cm) 100% were used in the study. Results showed that light availability on onion and garlic decreased with the increased of shade produced by brinjal canopy over the time up to 95 days after transplanting of onion seedling and planting of garlic cloves. In both the years, throughout the growing period of onion and garlic the maximum light availability was observed in T6 (sole onion) and T7 (sole garlic) treatments followed by T4 treatment (3 row garlic 43% in between two row of brinjal 100%) and T3 treatments (4 row garlic 57% in between two row of brinjal 100%) and the minimum light availability was observed in T1 treatment (4 row onion 57% in between two row of brinjal 100%) followed by T2 treatment (3 row onion 43% in between two row of brinjal 100%). Light availability was more in brinjal + garlic intercropping system than brinjal + onion intercropping system throughout the growing period. All the intercropping combinations showed better performance in terms of brinjal equivalent yield, gross return, gross margin and benefit cost ratio (BCR) over sole crops. Among the intercropping combination, 4 row garlic (15 cm × 10 cm) 57% in between two row of brinjal (80 cm × 60 cm) 100% was the agronomically most feasible and profitable intercropping system in respect of brinjal equivalent yield (36.42 t ha−1), land equivalent ratio (LER)1.29, gross return (Tk.7,28,333 ha−1), gross margin (Tk.4,76,596 ha−1) and benefit cost ratio (2.89).Bangladesh Agron. J. 2025, 28(1): 1-7